2012
DOI: 10.1177/1533317512456067
|View full text |Cite
|
Sign up to set email alerts
|

Gene–Environment Interaction in Alzheimer’s Disease

Abstract: GxE interactions exist with APOE ∈4 allele status that need to be considered for the study design and analysis of such data in future studies of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…The present study showed high frequency of ε4 allele in AD, which is in accordance with other findings (Thelma et al, 2001;Kapur et al, 2006;singh et al, 2012). The precise mechanisms by which APOE isoforms and lipids are involved in the pathogenesis of AD still remain unclear.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study showed high frequency of ε4 allele in AD, which is in accordance with other findings (Thelma et al, 2001;Kapur et al, 2006;singh et al, 2012). The precise mechanisms by which APOE isoforms and lipids are involved in the pathogenesis of AD still remain unclear.…”
Section: Discussionsupporting
confidence: 93%
“…The specific primers 5'-ACAGAATTCGCCCCGGCCTGGTAC-AC-3' and 5'-TAAGCTTGGCACGGCTGTCC AAGGA-3' were used for amplification (Singh et al, 2012). PCR assay was performed on Bio-Rad iQ5 cycler, USA, in a 20µl volume of 1x high-fidelity master mix (Bio-Rad) containing high-fidelity buffer, 0.04U/µl DNA polymerase, 1.5mM MgCl2, 200µM dNTPs.…”
Section: Apoe Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction of OCP residues was done by using HPLC- grade hexane and acetone (2 : 1) according to method of Singh et al [11]. Hexane (6 mL) and acetone (3 mL) were added and the contents were shaken at room temperature for 30 minutes in a mechanical shaker.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining portion was again extracted twice using the same process and the hexane fractions were added to the previous solvent fractions. Cleanup was done by USEPA method by column chromatography as described by Singh et al [11]. Florisil was activated at 130°C overnight and cooled in a dessicator before use.…”
Section: Methodsmentioning
confidence: 99%